Cross pollination response of loquat cv. 'Algerie' - Cuevas J.; Puertas M.; Hueso J.J. (First international symposium on loquat, 2003)
To explore cross-pollination response in loquat, we carried out controlled pollinations on 23 year-old trees, cv. 'Algerie'. Flowers of labelled shoots were bagged and either self- or cross-pollinated with a mixture of pollen from 'Tanaka' and 'Golden Nugget'. Control shoots were left exposed to open-pollination. Number and quality of the fruits formed were recorded for the three treatments. Results show that under experimental cross- and open-pollination higher fruit set can be obtained when compared with self-pollination. Despite a higher crop load, fruits obtained under open- and cross-pollination were also heavier and larger, with an increase in seed number, and advanced development. No variation in pulp-seed ratio was observed. Microscopy observations showed that self-incompatibility of 'Algerie' is not complete and matched effects of pollination treatments on seed number. Low fruit set under self-pollination suggests that arrival of pollen tubes to ovules may be an inadequate estimation for successful fertilization in this species.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)